Case Method Learning for Improving Critical Thinking Skills among Elementary School Students: Učenje z metodo primera pri izboljšanju sposobnosti kritičnega mišljenja osnovnošolcev: analiza potreb - Nafisah, Ainun; Marmoah, Sri; Riyadi, (Revija za elementarno izobraževanje, 2024)
This study aimed to analyse students’ critical thinking profiles and assess teachers’ needs for case method learning to improve critical thinking skills. The research method used was qualitative. The study’s results reveal that most students' mastered critical thinking skills profiles are indicators of reveals existing facts and drawing conclusions. However, indicators that students have not fully mastered critical thinking are formulating the key issues, selecting logical arguments, conducting analysis, and conducting evaluations. As a result, teachers require a learning method, precisely the case method, to encourage critical thinking skills.
Keywords: Case Method; Critical thinking; Elementary School